1999
DOI: 10.1165/ajrcmb.20.4.3404
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer and Past Occupational Exposure to Asbestos

Abstract: Studies on somatic mutations in lung cancers associated with cigarette smoking and asbestos exposure are few. We investigated prevalence of mutations in the p53 and K-ras genes in lung tumors from smokers with and without asbestos exposure at work. For K-ras mutations, the study was an extension of an earlier analysis. Nearly all of the 105 consecutive patients examined were smokers and had non-small-cell carcinoma of the lung with squamous-cell carcinoma or adenocarcinoma histology. Exposure to asbestos was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…26 For 58 of the cases, a specimen of nonmalignant peripheral lung tissue was also available for investigation. In addition, leukocyte DNAs from cancer patients (n ϭ 15) were examined.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 For 58 of the cases, a specimen of nonmalignant peripheral lung tissue was also available for investigation. In addition, leukocyte DNAs from cancer patients (n ϭ 15) were examined.…”
Section: Patientsmentioning
confidence: 99%
“…Data on occupational asbestos exposure were available for 61 patient, with 22 cases exposed to asbestos at work. 26 …”
Section: Patientsmentioning
confidence: 99%
“…43,44 KRAS mutations are shown to be associated with smoking history and asbestos exposure. 37,45 Incidentally, KRAS mutations are more prevalent in women than men. Nelson et al 37 reported that this association was statistically significant after adjustment for cigarette smoking and asbestos exposure, implicating a possible role of estrogen in either initiating or selectively targeting KRAS mutation sites in pulmonary adenocarcinoma.…”
Section: Kras Mutations and Morphology (Clinical And Histologic Corrementioning
confidence: 99%
“…In the genetic abnormality of asbestos-related lung cancer, mutations of the k-ras and TP53 (p53) have been reported [38][39][40][41][42][43][44][45][46][47][48] . K-ras mutation is an oncogene that plays an important role in the signal transduction of the epidermal growth factor receptor (EGFR).…”
Section: Genetic Abnormality Of Malignant Pleural Mesothelioma and Lumentioning
confidence: 99%